Fortalecimiento de la audio-perceptiva a través de la formación de la orquesta pedagógica de percusión menor en los niños de primer año del colegio de artes ‘‘salvador Bustamante Celi - Patiño Armijos, Carolina Michelle (2022)
The teaching-learning process of audio-perception has gone through significant changes, from various experiences developed in order to improve and perfect it. New forms and methodologies focused on its optimization have been experimented with. As the following research work exposes and taking as a methodological instrument ''The formation of a Minor Percussion Pedagogical Orchestra''. The main objective has been proposed to strengthen the musical language of the first-year children of the "Salvador Bustamante Celi" College of Arts through the formation of a Minor Percussion Pedagogical Orchestra, to develop skills (musical and non-musical) of working together. When talking about the orchestra, we are referring to the wonderful optimizing method in terms of musical learning (audio-perceptive) such as: learning to listen, recognize, sing, clap themes, harmonic, melodic and rhythmic independence. Since, when music is conceived from within an orchestra, there is communication, feedback and cooperation, in a common good ''the final work'', that is, the criterion is examined, which tries, wishes or the director believes it appropriate. The conductor represents the key figure and guide towards the development of the interpretive and intentional musical idea of the composer. In other words, orchestra training is not only limited to the musical area only, but is conceived as broad, inclusive and participatory; since since its execution, children develop both musical and non-musical skills. The methodology that was used for its development is made up of scientific, analytical, synthetic and hermeneutic methods; aimed at knowing, understanding, describing, analyzing, interpreting, verifying, delimiting, developing, demonstrating and presenting new knowledge. 5 Next, the instruments that accompanied the investigative process: Interviews applied to the Rector, Vice-Rector and Head of the Rhythmic and Audio-perceptive Education subjects and Pedagogical Orchestra of the College of Arts ''Salvador Bustamante Celi'' (three people). Subsequently, surveys were carried out, which were addressed to the teachers of the subjects of Pedagogical Orchestra and Rhythmic and Audio-perceptive Education of the first year of the College of Arts ''Salvador Bustamante Celi'' (three people), giving a total population of six people. With the purpose of evidencing the feasibility of the research work, for its interpretation of two works, four students of the first year of the College of Arts participated ‘‘Salvador Bustamante Celi’’, who carried the lines of indeterminate percussion. For the execution of the melodic lines, three students from the percussion area collaborated. Where we obtained as a result that the Pedagogical Orchestra of Minor Percussion strengthens the teaching-learning process of musical language in infants since by this means it is possible to develop their auditory, melodic, rhythmic, interpretive harmonic, assembly and coordination capacity. In view of the above, it is recommended to put into operation the Minor Percussion Pedagogical Orchestra and integrate it with all the children of the first year, regardless of their level of knowledge, musical ability or efficiency when learning, seeking their total inclusion, integration and education.